Explorando o déficit em saneamento no Brasil: evidências da disparidade urbano-rural - Silveira, André Braga Galvão (2013)
The characterizations of the Brazil’s lack of access to basic sanitation have been historically performed considering levels of data disaggregation which do not enable to know in detail the spatial distribution of access. Using microdata from the 2010 IBGE Census, this paper aims to explore the differences between basic sanitation access and coverage considering urban and rural areas, disaggregated to the municipality level. In addition, indicators to measure the degree of inequality between urban and rural deficits were created. For the presentation of the results, thematic maps, tables and graphs were used. The conclusion was that there are substantial differences in the access to basic sanitation between rural and urban areas of Brazil. In general, rural areas have the worst indicators in all analyzed variables. Besides, regions that do not show expressive deficits in rural basic sanitation, were found to have great iniquities in urban-rural comparison.